EVALUATION OF THE INFLUENCE OF INTEREST RATE ON PRIVATE DOMESTIC INVESTMENT IN NIGERIA - Eze, Onyebuchi Michael; Nweke, Abraham Mbam; Ubaka, Chika Kingsly; Anyiema, Benjamin Ifeakachukwu (EBSU Journal of Social Sciences and Humanities, 2024)
The study evaluated the effect of interest rates on private domestic investment in Nigeria from 1986 to 2019. The paper employed the Auto-Regressive Distributed Lag model in the analysis. To achieve robust results, the study conducted a structural break test in the time series and co-integration analysis. The main findings of the study were that interest rates had a negative and significant effect on private domestic investment in both the short run and the long run. It was also revealed that interest rates had multiple structural breaks in the years 2002, 2009 and 2014, respectively. The study recommended that the monetary authorities should utilize the monetary policy, the interest rate, in particular, to promote private domestic investment by keeping interest rates low. In so doing, private domestic investment will improve leading to increased employment, productivity, and growth of the economy.